Two-parameter Lévy processes: ItÔ formula, semigroups, and generators - Mishura, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We consider random Lévy fields, i.e., stationary fields continuous in probability and having independent increments. We prove that the trajectories of such fields have at most one jump on every line parallel to the axes. We derive an expression for the ItÔ change of variables for Lévy fields. We also consider semigroups generated by Lévy fields and their generators.